Treatment selection for patients with relapsed or refractory follicular lymphoma - Skarbnik, Alan Z.; Patel, Krish (Frontiers in Oncology, 2023)
Follicular lymphoma (FL) is the second most common lymphoma in the United States and is characterized by a variable clinical course, disease heterogeneity, and a relapse-and-remittance pattern historically accompanied by successive shortening of clinical response with every line of treatment. Factors such as progression of disease within 24 months of initial treatment are associated with poor survival outcomes. Although rituximab-based regimens are preferred for early lines of treatment, no clear standard of care exists for treatment of FL in the third-line setting or later as approved third-line treatments have not been compared in a prospective, randomized clinical trial. Rather, physicians may choose from several therapeutic classes with different safety profiles and dosing regimens, with consideration of patient and disease factors. Here we describe 2 hypothetical patients with relapsing or remitting FL, an elderly patient with comorbidities, and a younger patient whose FL progressed within 24 months. These cases are used to highlight key factors that clinicians should consider when selecting therapies for relapsed or refractory FL, such as patient frailty, age, comorbidities, as well as quality of life and patient-specific preferences for less intrusive treatment regimens or longer remission times.